Representation dimension of generalized path algebras of cyclic quivers. Issue 6 (3rd June 2017) - Eshraghi, Hossein
ABSTRACT: Let Λ be a non semisimple symmetric artin algebra over a commutative artinian ring R and let repdim ( Λ ) be its representation dimension. Assume also that 𝒬 is a finite quiver whose connected components are amalgamations of single cycles possibly with multiple arrows, and that ℐ is an admissible ideal in the generalized path algebra Λ 𝒬 . We prove that r e p d i m ( Λ 𝒬 ℐ ) ≤ repdim ( Λ )+1.